49 Burden and challenges of malignant bowel obstruction: a qualitative study. (30th January 2023) - Baddeley, Elin; Bravington, Alison; Nelson, Annmarie; Johnson, Miriam J; Murtagh, Fliss EM; Currow, David C; Obita, George; Boland, Elaine G; Seddon, Kathy; Oliver, Alfred; Noble, Simon IR; Boland, Jason W
Abstract : Introduction: Malignant bowel obstruction (MBO) is a distressing complication of cancer, causing symptoms including nausea, vomiting, pain, and constipation. It has a profound effect on quality of life, often requiring hospitalisation. There is a lack of data indicating how outcomes used to evaluate MBO in research and clinical practice are related to the patient experience, and what key features are important to them and their caregivers. Aims: To explore key features of the lived experience of people with MBO, their caregivers, and perspectives of healthcare professionals. Methods: Semi-structured interviews with people with MBO, their caregivers and healthcare professionals who manage this condition. Data were analysed using thematic analysis. Results: Eight people with MBO, two caregivers and 19 healthcare professionals were interviewed. Five themes were generated: 1. Symptom and treatment burden; 2. Psychological, social and functional implications; 3. Complexities and challenges of care (variability and uncertainty of management outcomes); 4. Collaborative care and communication; and 5. Nature and trajectory of MBO. The interviews highlight the devastating impact of symptoms of MBO, and side effects of treatment. MBO affected psychological, social and functional aspects of patients' quality of life. Healthcare professionals described the complex challenges of managing MBO, from uncertain guidelines to the variability of each individual case and the difficulties surrounding communication of a diagnosis of MBO, and its impact. Conclusions: These findings highlight the challenges posed for healthcare professionals managing MBO, and the high burden of symptoms on patients and caregivers, including psychological and social impact on patients' quality of life. Patient-relevant goals of care should be collaboratively explored and understood by practitioners, patients and caregivers. Impact: Outcomes from these interviews have been used to inform a core outcome set for inoperable MBO, focused on prioritising patient-relevant outcomes that should be measured in research and clinical practice.